Peningkatan Kemampuan Menulis Teks Tanggapan Melalui Strategi Menulis Terbimbing Berbantuan Lagu 'Masih Ada Waktunya' Pada Murid Kelas 7c Smpn 17 Malang - Syaharani Setyo Prameswari; Wadji Wadji; Chusnaini Chusnaini (Universitas Pakuan, 2026)
IMPROVING THE ABILITY TO WRITE RESPONSE TEXTS THROUGH GUIDED WRITING STRATEGIES HELPED BY THE SONG 'STILL THERE'S TIME' IN CLASS 7C STUDENTS OF SMPN 17 MALANG IN THE 2025/2026 ACADEMIC YEAR The reasons for the low ability to write response texts of seventh-grade students at SMPN 17 Malang include traditional learning methods, limited sources of inspiration, and a lack of creative ideas, which cause boredom and laziness. This classroom action research (CAR) aims to improve students' ability to write response texts by implementing a Guided Writing Strategy (SMT) with the source of inspiration from the song